Energy and Exergy analysis of raw material preparation in a cement production plant (2010)
The production process of a major wet process cement manufacturing plant in Nigeria was studied and data collected for a five year period 2001 - 2005, from them enabled the estimation of the embodied energy intensity, exergy efficiency and the environmental impact of the raw material preparation process was assessed. The cement plant accounts for over 40% of total local production of cement in Nigeria. The Input - Output energy analysis methodology was used to evaluate the embodied energy intensity which was found to decrease over the period by 35% from 91.7 kWh/t to 57.6kWh/t, this embodied intensity was over 70% higher than the best recommended global practice of 18 - 20kWh/t. Exergy analysis was used to evaluate the exergy efficiency of the raw material preparation and this increased marginally from 45 - 49% over the period, compared to best global practices of 50% this was found to be optimum. CO2 and CO are two major greenhouse gas emitted during the raw material preparation process, however there was a 20% reduction in their emission over the study period.